Proceedings of the first meeting of the Operational Research (OR) Society's Special Interest Group on Agriculture and Natural Resources (SIG-ANR) - Sandars, D. L. (Cambridge University Press, 2010)
This group, which represents the reformed Operational Research (OR) Society's Agriculture and Related Industries group (http://www.orsoc.org.uk), promotes the use of OR (or the application of the scientific method) in solving management and governance problems within this sector. The theme of this meeting was to look at models concerned with making better decisions for the management or governance of the agricultural and natural resource industries. This first one day meeting was at Reading University, Berkshire, UK on the 2 April when the following papers were read.